Manfaat Digitalisasi Sebagai Sumber Belajar Dalam Meningkatkan Proses Pembelajaran Anak Usia Dini - Irma Yuliantina; Susy Anggriani (Universitas Islam Lamongan, 2025)
The development of digital technology today is increasingly rapid, teachers use digital tools for various purposes. Through the digitization system, it will speed up and make it easier for teachers to get various information related to teaching materials, so that the learning process and objectives will be achieved optimally. This study aims to understand the benefits of digitalization as a learning resource in improving the early childhood learning process. The methodology in this study uses descriptive qualitative, researchers try to describe and interpret teacher perceptions in relation to the benefits of digitalization as a learning resource in improving the early childhood learning process. From the results of the study, a significant comparison was obtained between the use of digitalization as a learning resource with the improvement of the early childhood learning process. This is reinforced by the average percentage of digitalization utilization of 93.63% directly proportional to the increase in the learning process of 97.01%. Teacher respondents as children's learning companions gave positive approval that there was an improvement in the learning process by utilizing digitalization as a learning resource. The use of digitalization as a learning resource is proven to improve the process of quality child learning. The use of digital tools can help in meeting children's learning needs according to the characteristics and stages of early childhood development.